2022
DOI: 10.1371/journal.pone.0275634
|View full text |Cite
|
Sign up to set email alerts
|

Quality of endodontic record-keeping and root canal obturation performed by final year undergraduate dental students: An audit during the COVID-19 pandemic

Abstract: Background To assess the quality of endodontic record-keeping and root canal obturation performed by undergraduate final year dental students during the COVID-19 pandemic. Materials and methods Dental records and dental radiographs of patients who received endodontic treatments between March 2020 and March 2022 by undergraduate students during the COVID-19 pandemic were included. The audit data were collected based on the European Society of Endodontology guidelines retrospectively via assessing the patient’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…This observation is consistent with some of the previous studies [ 2 , 13 ]. Different order was observed in other studies where premolars were the most restored teeth followed by anteriors [ 3 , 5 , 15 ]. Few cases in this study showed insufficient apical seal (<3 mm), and they were mainly found in the anterior and premolars.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…This observation is consistent with some of the previous studies [ 2 , 13 ]. Different order was observed in other studies where premolars were the most restored teeth followed by anteriors [ 3 , 5 , 15 ]. Few cases in this study showed insufficient apical seal (<3 mm), and they were mainly found in the anterior and premolars.…”
Section: Discussionmentioning
confidence: 57%
“…One of the most common clinical procedures that general dentists can perform daily is post-preparation [ 3 ]. An effective apical seal is important to obtain a successful endodontic treatment, and it is crucial to remain intact during post space preparation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations